2011
DOI: 10.1007/s11999-010-1614-z
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Segmental Alignment as Predictor of Adjacent-Level Degeneration After a Cloward Procedure

Abstract: Background The Cloward anterior interbody fusion is commonly performed for cervical disc herniation or spondylosis. In followup studies, various authors have noted clinically relevant adjacent-level degeneration. However, factors associated with adjacent-level degeneration are not well known. Questions/purposes We asked whether the postoperative sagittal segmental alignment of the fused vertebrae could be used as a predictor of adjacent-level degeneration. Methods We retrospectively studied 107 patients, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…Faldini et al reported that the Cloward procedure was a reasonable technique for the treatment of cervical disc herniation. To prevent ASD, it was recommended to maintain a lordotic SSA, which would be considered a protective factor against ASD [16,17]. In the current study, a comparison between preoperative and follow-up SSA and SACS angles proved the effectiveness of the procedure in correcting cervical sagittal misalignment when degenerative changes lead to cervical spine straightening or cervical kyphosis.…”
Section: Discussionmentioning
confidence: 62%
“…Faldini et al reported that the Cloward procedure was a reasonable technique for the treatment of cervical disc herniation. To prevent ASD, it was recommended to maintain a lordotic SSA, which would be considered a protective factor against ASD [16,17]. In the current study, a comparison between preoperative and follow-up SSA and SACS angles proved the effectiveness of the procedure in correcting cervical sagittal misalignment when degenerative changes lead to cervical spine straightening or cervical kyphosis.…”
Section: Discussionmentioning
confidence: 62%
“…Park et al [15] suggested that malalignment of the cervical spine following anterior cervical surgery affects the development of clinical adjacent segment pathology [6] found that malalignment after cervical arthrodesis promotes degenerative changes at levels adjacent to fused segments; adjacent segment degeneration was found in 27 and 60 % of cases fused in lordosis or kyphosis, respectively. Katsuura et al [9] evaluated 42 patients that underwent anterior cervical interbody fusion surgery using lateral radiographs of the cervical spine, and diagnosed radiographically adjacent segment pathology when radiographic findings were consistent with symptoms and signs.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between HRQOL and sagittal spinal alignment parameters, including spinopelvic parameters, have been previously reported, and some authors have reported on the importance of cervical sagittal balance [6,9,15]. However, no relationships have been established between cervical sagittal alignment and HRQOL in AS.…”
Section: Introductionmentioning
confidence: 99%
“…After surgery, standard radiographs of the cervical spine were performed. Postoperative immobilization consisted of a neck collar for 40 days [10,16]. At follow-up, patients were rated from excellent to poor depending on resolution, improvement, or persistence of preoperative symptoms according to Odom et al [2].…”
Section: Methodsmentioning
confidence: 99%
“…Cervical fusion by anterior approach was first described by Robinson and Smith [5] and by Cloward [6,7]. These techniques have been widely used by many authors, with satisfactory short-term results [8][9][10]. The aim of this study was to report the clinical and radiological results of 107 patients operated by discectomy and onelevel anterior cervical fusion according to the Cloward procedure, with a minimum 10-year follow-up.…”
Section: Introductionmentioning
confidence: 99%